2010
DOI: 10.1089/end.2010.0223
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Experience in the Management of Angiomyolipoma

Abstract: AML is a renal tumor that usually exhibits a benign course. Surgical removal and embolization are the standard invasive treatment modalities. AS for AMLs is associated with a slow and consistent growth rate (0.088 cm/year), typically has minimal morbidity, and is a reasonable option in selected patients. Symptomatic presentation and size (> 3 cm) are not predictive for necessitating an invasive procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 16 publications
2
62
0
2
Order By: Relevance
“…As a benign lesion, most renal AMLs are asymptomatic, have a slow and consistent growth rate and minimal morbidity (19). They often do not require any intervention.…”
Section: Introductionmentioning
confidence: 99%
“…As a benign lesion, most renal AMLs are asymptomatic, have a slow and consistent growth rate and minimal morbidity (19). They often do not require any intervention.…”
Section: Introductionmentioning
confidence: 99%
“…3 Angiomyolipomata are benign, however size increase of 0.088-0.427 cm/year is reported, and can result in mass effect. 4,5 Distorted vascular architecture can additionally predispose angiomyolipoma to active retroperitoneal hemorrhage. 6 Angiomyolipoma has a prevalence of 0.02-0.1% in males, and 0.22-0.29% in females.…”
Section: Introductionmentioning
confidence: 99%
“…Several retrospective series have shown the feasibility of AS for AML. [52][53][54][55] The identification of clinical predictors showing the need for delayed active treatment, thus allowing to minimize the risk of spontaneous complications, would be extremely useful in AS protocols. With the aim to answer this relevant question, Ouzaid et al reported outcomes from a retrospective cohort of 130 patients diagnosed with AML on computed tomography imaging and managed with AS at the Glickman Urological and Kidney Institute.…”
Section: As For Benign Tumor (Angiomyolipoma)mentioning
confidence: 99%
“…56 These results are comparable with those reported in the smaller series by De Luca et al 53 Conversely, Mues et al did not find statistically significant correlations between clinical predictors (such as tumor dimension, growth rate or symptoms) and the need for active treatment. 52 In that study, among 91 patients diagnosed with AML, 48 were placed on AS as primary management. At a median follow up of 54.8 months, AS failed only in three patients because of retroperitoneal bleeding or fast growth rate (0.7 cm/year).…”
Section: As For Benign Tumor (Angiomyolipoma)mentioning
confidence: 99%
See 1 more Smart Citation